Budapest: A Place Where Cultures Meet Continuously - Bubak, Grzegorz (Media - Culture - Social Communication, 2019)
Almost throughout its history representatives of different nationalities have come to Budapest. Migration was determined by economic, social and political causes. In this paper I will try to analyze the problem of the clash of cultures in some Hungarian films. I discuss feature films in which the city is not only the background. I believe that the key to show the multicultural capital of Hungary, the processes occurring as a result of the meeting, or the collision of different cultures is the chronology. The flow of time highlights the variability of the phenomena, further problems somehow solve themselves, and they are replaced by new ones. The film directors focus on important moments in Hungarian history in which a key role was played by a period of systemic change.